Democratic Pluralism and Political Unity in the Anthropocene - Arias-Maldonado, Manuel Jesús (My University, 2023)
The question of social and political pluralism takes on a new dimension in the wider context of the Anthropocene. Keeping the planet hospitable for human beings requires a considerable social effort. To such end, the anthropogenic impact on natural systems must be reduced. How is this to be done? Individual actions acquire a systemic dimension once they are globally aggregated to others — private choices have public consequences. If the dangerous trend of the Earth system is to be corrected, then, the political question of social pluralism comes to the fore: what behaviors, identities and forms of life are permissible in the Anthropocene? Must pluralism be sacrificed on account of the need to survive as a species? Or perhaps pluralism may be expected to flourish in degrowth societies that restrict their material output? I will suggest that pluralism is an asset rather than a burden for governing the Anthropocene. But it will hardly be preserved in the kind of small communities advocated by degrowthers. I will argue that a liberal-democratic approach to global sustainability is a better option for balancing individual autonomy and collective survival. I will also ponder whether the danger of an uninhabitable planet may provide contemporary democratic societies a common goal, i.e., a motive around which some kind of collective understanding can be built up — or whether this subject will instead reinforce the polarization and division of the body politic.
Keywords: Pluralismo (Ciencias sociales); Antropoceno; Democracia; Pluralismo; Decrecimiento; Sostenibilidad